Analysis of Perceived Benefits of Breast Milk Towards Exclusive Breastfeeding in Stunting Prevention - Risna Mona Aristin; Nur Alam Fajar; Muhammad Cholil Munadi; Esti Sri Ananingsih; Rini Sugiarti (Association of Public Health Scholars based in Faculty of Public Health, Sriwijaya University, 2024)
Stunting is a condition of growth failure due to accumulated nutritional inadequacies from prenatal until two years old. Individuals' perceptions of perceived benefits influence exclusive breastfeeding and thus reduce the risk of stunting. This study aimed to analyze the perception of the benefits of breastfeeding in preventing stunting in Tuah Negeri District, Musi Rawas Regency. The research method used a quantitative approach with a cross-sectional design. Sampling using purposive sampling technique resulted in 154 respondents aged 6-36 months. Data analysis used frequency distribution, chi-square test, and logistic regression test. Univariate results, good attitude (perceived benefits) 58.4%, high knowledge 66.2%, not good practices 57.1%, age <30 years 50.6%, low education 55.2%, not working 86.4%, family income below minimum wage 93.5% and number of family members ≤4 57.1%. Mothers’ knowledge has a relationship with exclusive breastfeeding practices (p<0.05) However, there was no relationship between perceived benefits of breastmilk reflected through attitudes and exclusive breastfeeding practices, as well as age, education, occupation, income and number of family members. Multivariate showed that low mothers’ knowledge had a 3.1 times higher risk of have unfavorable practices in exclusive breastfeeding, controlled by mother’s education. Based on study, the government needs to conduct education and long-term approaches through formal education so that mothers better understand health information.